Visualized Analysis of Heavy Ion Radiotherapy: Development, Barriers and Future Directions - Jin, Yuanchang; Li, Jingwen; Li, Jieyun; Zhang, Na; Guo, Kangle; Zhang, Qiuning; Wang, Xiaohu; Yang, Kehu (Frontiers in Oncology, 2021)
Background: Heavy ion radiotherapy (HIRT) has great advantages as tumor radiotherapy. Methods: Based on 1558 literatures from core collections of Web of Science from 1980 to 2020, this study visually analyzes the evolution of HIRT research, and sorts out the hotspots and trends of HIRT research using CiteSpace software. Results: Research on HIRT has received more extensive attention over the last 40 years. The development of HIRT is not only closely related to radiation and oncology, but also closely related to the development of human society. In terms of citation frequency, “International Journal of Radiation Oncology*Biology*Physics” was the top journal. In terms of influence, “Radiotherapy and Oncology” was the top journal. “Radiation therapy” and “carbon ion radiotherapy” were the two most frequently used keywords in this field. Conclusion: The evolution of the HIRT research has occurred in approximately three stages, including technological exploration, safety and effectiveness research and technological breakthroughs. Finally, some suggestions for future research are put forward.